Quasiparticle and excitonic effects in the optical spectra of diamond, SiC, Si, GaP, GaAs, InP, and AlN - Hahn, P. H.; Seino, K.; Schmidt, Wolf Gero; Furthmüller, J.; Bechstedt, F. (physica status solidi (b))

VUV-ellipsometry on GaN: Probing conduction band properties by core level excitations - Esser, N.; Rakel, M.; Cobet, C.; Schmidt, Wolf Gero; Braun, W.; Cardona, M. (physica status solidi (b))

Initial Stage of Si(001) Surface Oxidation from First-Principles Calculations - Fuchs, F.; Schmidt, Wolf Gero; Bechstedt, F. (The Journal of Physical Chemistry B)

Understanding the optical anisotropy of oxidized Si(001) surfaces - Fuchs, F.; Schmidt, Wolf Gero; Bechstedt, F. (Physical Review B)

Coulombic Amino Group-Metal Bonding: Adsorption of Adenine on Cu(110) - Preuss, M.; Schmidt, Wolf Gero; Bechstedt, F. (Physical Review Letters)

Conformation-selective adsorption of 2,3-butanediol on Si(001) - Seino, K.; Schmidt, Wolf Gero (Surface Science)

Second-harmonic polarizability including electron-hole attraction from band-structure theory - Leitsmann, R.; Schmidt, Wolf Gero; Hahn, P. H.; Bechstedt, F. (Physical Review B)

Optical response ofπ-conjugated molecular monolayer adsorbed on the semiconductor Si(001) surface: A first-principles study - Hermann, A.; Schmidt, Wolf Gero; Bechstedt, F. (Physical Review B)

Phenanthrenequinone Adsorbed on Si(001): Geometries, Electronic Properties, and Optical Response - Hermann, Andreas; Schmidt, Wolf Gero; Bechstedt, Friedhelm (The Journal of Physical Chemistry B)

Optical Absorption of Water: Coulomb Effects versus Hydrogen Bonding - Hahn, P. H.; Schmidt, Wolf Gero; Seino, K.; Preuss, M.; Bechstedt, F.; Bernholc, J. (Physical Review Letters)

Molecular electronic excitations calculated from a solid-state approach: Methodology and numerics - Hahn, P. H.; Schmidt, Wolf Gero; Bechstedt, F. (Physical Review B)

Ga-Rich Limit of Surface Reconstructions on GaAs(001): Atomic Structure of the(4×6)Phase - Ohtake, Akihiro; Kocán, Pavel; Seino, Kaori; Schmidt, Wolf Gero; Koguchi, Nobuyuki (Physical Review Letters)

H2O on Si(001): surface optical anisotropy from first-principles calculations - Seino, K.; Schmidt, Wolf Gero (Surface Science)

Oxidation- and organic-molecule-induced changes of the Si surface optical anisotropy:ab initiopredictions - Schmidt, Wolf Gero; Fuchs, F; Hermann, A; Seino, K; Bechstedt, F; Paßmann, R; Wahl, M; Gensch, M; Hinrichs, K; Esser, N; Wang, S; Lu, W; et al. (Journal of Physics: Condensed Matter)

The Bethe–Salpeter equation: a first-principles approach for calculating surface optical spectra - Palummo, M; Pulci, O; Sole, R Del; Marini, A; Hahn, P; Schmidt, Wolf Gero; Bechstedt, F (Journal of Physics: Condensed Matter)

Methylchloride adsorbed on Si(001): an ab initio study - Preuss, M; Schmidt, Wolf Gero; Seino, K; Bechstedt, F (Applied Surface Science)

Atomic indium nanowires on Si(111): the (4 × 1)–(8 × 2) phase transition studied with reflectance anisotropy spectroscopy - Fleischer, K; Chandola, S; Esser, N; Richter, W; McGilp, J.F; Schmidt, Wolf Gero; Wang, S; Lu, W; Bernholc, J (Applied Surface Science)

Energetics of Si(001) Surfaces Exposed to Electric Fields and Charge Injection - Seino, K.; Schmidt, Wolf Gero; Bechstedt, F. (Physical Review Letters)

Methyl Chloride Adsorption on Si(001)−Electronic Structure - Preuss, M.; Schmidt, Wolf Gero; Bechstedt, F. (The Journal of Physical Chemistry B)

Organic modification of surface electronic properties: A first-principles study of uracil on Si(001) - Seino, K.; Schmidt, Wolf Gero; Bechstedt, F. (Physical Review B)

Calculation of surface optical properties: from qualitative understanding to quantitative predictions - Schmidt, Wolf Gero; Seino, K.; Hahn, P.H.; Bechstedt, F.; Lu, W.; Wang, S.; Bernholc, J. (Thin Solid Films)

Reflectance anisotropy of uracil covered Si(001) surfaces: Ab initio predictions - Seino, K.; Schmidt, Wolf Gero (Surface Science)

Ground- and excited-state properties of DNA base molecules from plane-wave calculations using ultrasoft pseudopotentials - Preuss, M.; Schmidt, Wolf Gero; Seino, K.; Furthmüller, J.; Bechstedt, F. (Journal of Computational Chemistry)

Many-body and overlayer effects on surface optical properties - Bechstedt, F.; Del Sole, R.; Glutsch, S.; Hahn, P. H.; Pulci, O.; Schmidt, Wolf Gero (physica status solidi (b))

Gallium-rich reconstructions on GaAs(001) - Pristovsek, M.; Tsukamoto, S.; Ohtake, A.; Koguchi, N.; Orr, B. G.; Schmidt, Wolf Gero; Bernholc, J. (physica status solidi (b))

Cycloaddition reaction versus dimer cleavage at theSi(001):C5H8interface - Lu, Wenchang; Schmidt, Wolf Gero; Bernholc, J. (Physical Review B)

Layer-by-layer analysis of surface reflectance anisotropy in semiconductors - Castillo, C.; Mendoza, Bernardo S.; Schmidt, Wolf Gero; Hahn, P. H.; Bechstedt, F. (Physical Review B)

Nanowire-induced optical anisotropy of the Si(111)-In surface - Wang, Shuchun; Lu, Wenchang; Schmidt, Wolf Gero; Bernholc, J. (Physical Review B)

P-richGaP(001)(2×1)/(2×2)surface: A hydrogen-adsorbate structure determined from first-principles calculations - Hahn, P. H.; Schmidt, Wolf Gero; Bechstedt, F.; Pulci, O.; Del Sole, R. (Physical Review B)

Pyrrole (C4H4NH) and Polypyrrole Functionalized Silicon Surfaces Calculated from First Principles - Schmidt, Wolf Gero; Seino, K. (Surface Review and Letters)
The functionalization of the Si(001) surface by pyrrole and polypyrrole is investigated by means of first-principles pseudopotential calculations. We find dissociative reactions, leading to the partial fragmentation of the molecule, to be energetically most favored for pyrrole adsorption. The lowest-energy configuration for monolayer coverage is characterized by pyrrole rings bonded to the surface via Si–N linkage. In coexistence with adsorption geometries where both N and C are bonded to the surface, this structure accounts very well for the available experimental data. Chemisorption of pyrrole is found to effectively passivate the Si(001) surface, irrespective of the details of the adsorption geometry. The formation of well-ordered polypyrrole structures on Si(001) may require chemical modifications of the polypyrrole chains in order to account for the lattice mismatch.

Surface Ordering of P-rich InP(001): Hydrogen Stabilization vs Electron Correlation - Hahn, P. H.; Schmidt, Wolf Gero (Surface Review and Letters)
The influence of hydrogen on the reconstruction of InP(001) surfaces is studied by first-principles calculations. One-monolayer phosphorus forming oppositely buckled dimers with one hydrogen adsorbed per dimer is energetically favored for a wide range of surface preparation conditions. The electronic structure and STM image calculated for this adsorbate geometry agree well with the experimental findings obtained after annealing of MOVPE-grown InP samples. The Si(001)-like surface ordering as well as the surface band gap of more than 1 eV, supposedly arising from electron correlation effects [Li et al., Phys. Rev. Lett.82, 1879 (1999)], are naturally explained by the hydrogen-stabilized surface structure favored by the total-energy calculations.

Uracil Adsorbed on Si(001): Structure and Energetics - Seino, K.; Schmidt, Wolf Gero; Preuss, M.; Bechstedt, F. (The Journal of Physical Chemistry B)

InP(001)-(2×1) Surface: A Hydrogen Stabilized Structure - Schmidt, Wolf Gero; Hahn, P. H.; Bechstedt, F.; Esser, N.; Vogt, P.; Wange, A.; Richter, W. (Physical Review Letters)

EfficientO(N2)method to solve the Bethe-Salpeter equation - Schmidt, Wolf Gero; Glutsch, S.; Hahn, P. H.; Bechstedt, F. (Physical Review B)

Chemisorption of pyrrole and polypyrrole on Si(001) - Seino, K.; Schmidt, Wolf Gero; Furthmüller, J.; Bechstedt, F. (Physical Review B)

Interplay of surface reconstruction and surface electric fields in the optical anisotropy of GaAs(001) - Schmidt, Wolf Gero; Bechstedt, F.; Lu, W.; Bernholc, J. (Physical Review B)

Structure and energetics of Ga-rich GaAs() surfaces - Seino, K.; Schmidt, Wolf Gero; Bechstedt, F.; Bernholc, J. (Surface Science)

GaAs(001) surface reconstructions: geometries, chemical bonding and optical properties - Schmidt, Wolf Gero; Bechstedt, F.; Bernholc, J. (Applied Surface Science)

III-V compound semiconductor (001) surfaces - Schmidt, Wolf Gero (Applied Physics A: Materials Science & Processing)

Bulk Excitonic Effects in Surface Optical Spectra - Hahn, P. H.; Schmidt, Wolf Gero; Bechstedt, F. (Physical Review Letters)

GaAs(001): Surface Structure and Optical Properties - Schmidt, Wolf Gero; Bechstedt, F.; Fleischer, K.; Cobet, C.; Esser, N.; Richter, W.; Bernholc, J.; Onida, G. (physica status solidi (a))

Towards a Complete Many-Body Description: Optical Response of Real Surfaces - Bechstedt, F.; Schmidt, Wolf Gero; Hahn, P.H. (physica status solidi (a))

Theory for Modeling the Optical Properties of Surfaces - Onida, G.; Schmidt, Wolf Gero; Pulci, O.; Palummo, M.; Marini, A.; Hogan, C.; Del Sole, R. (physica status solidi (a))

X-ray diffraction analysis of the gallium-rich surface of GaAs(001) - Paget, D.; Garreau, Y.; Sauvage, M.; Chiaradia, P.; Pinchaux, R.; Schmidt, Wolf Gero (Physical Review B)

First-principles study of InP and GaP(001) surfaces - Pulci, O.; Lüdge, K.; Vogt, P.; Esser, N.; Schmidt, Wolf Gero; Richter, W.; Bechstedt, F. (Computational Materials Science)

On the origin of resonance features in reflectance difference data of silicon - Hingerl, K; Balderas-Navarro, R.E; Bonanni, A; Tichopadek, P; Schmidt, Wolf (Applied Surface Science)

Terrace and step contributions to the optical anisotropy of Si(001) surfaces - Schmidt, Wolf Gero; Bechstedt, F.; Bernholc, J. (Physical Review B)

Optical Anisotropy of theSiC(001)-(3×2)Surface: Evidence for the Two-Adlayer Asymmetric-Dimer Model - Lu, Wenchang; Schmidt, Wolf Gero; Briggs, E. L.; Bernholc, J. (Physical Review Letters)

Atomic structure and optical anisotropy of III–V(001) surfaces - Esser, N.; Schmidt, Wolf Gero; Cobet, C.; Fleischer, K.; Shkrebtii, A. I.; Fimland, B. O.; Richter, W. (Journal of Vacuum Science & Technology B: Microelectronics and Nanometer Structures)

Structure and Energetics of P-rich GaP(001) Surfaces - Pulci, O.; Schmidt, Wolf Gero; Bechstedt, F. (physica status solidi (a))